STORE IN STORE FRANCHISING STRATEGY: THE TREND IN FRANCHISING NEGOTIATION - Rosado-Serrano, Alexander (2016)
The literature on franchising has traditionally focused on the effects and transformation it has promoted in the service sector, retailing, restaurants, hotels and other service-related industries. Store within a store research has been focused on the perspective of the manufacturer entering department stores. To date, little research has been carried out for the store in store strategy from the franchising perspective. This paper explores why big box retailers such as Walmart are adopting the store in store franchising strategy with specific partnerships with service firms such as McDonald's and Subway and how store in store franchising can be a new strategy for SMEs to expand. A content analysis methodology is used to interpret documents form Walmart Realty and specialized professional retail and quick service restaurants (QSR) magazines. The findings indicate that big box retailers such as Walmart choose to select the store in store franchising strategy to complement their shopping experience thru the boutique approach of complementing services in which they don't want to compete and increase their value proposition. Our findings also indicate that franchisor's choose the store in store franchising strategy due to the operational capabilities it acquires thru leasing space and high traffic availability that operating inside the big box store provides. We also suggest that store in store franchising strategy can be a new entry strategy for Family Enterprises and SMEs.